The Accidental Werewolf 2 : Something About Harry - Cassidy, Dakota (Cassidy, Dakota. Accidental series., 2013)
"He's in a furry situation. Accountant Harry Ralph Emerson has always been a by-the-numbers kind of guy. But when he finds himself trapped at work sprouting an obscene amount of hair, he knows his odds for maintaining normalcy are zero to none. After a frantic internet search, Harry goes through the OOPS--Out in the Open Paranormal Support--checklist and comes to a disheartening conclusion: He's turning into a werewolf and he needs help ASAP. She might be the only solution. Werewolf Mara Flaherty has long carried a torch for Pack Cosmetics's sexy single accountant, even after her attempt to seduce him went down in flames. When her sister-in-law, Marty, shows up to handle Harry's OOPS emergency, she tasks Mara with showing the hirsute hottie the ropes. But Mara knows Harry's condition is a result of her lab experiment gone wrong--and the previously mild-mannered object of her affection is about to give her a piece of his mind... "--